Weighing the Impacts of Airbnb in Iceland: Multivariate Perspectives - Gorlick, Alexa (FHSU Scholars Repository, 2020)
This research sought to evaluate if the sharing economy leader, Airbnb, creates impacts that residents of Iceland feel they experience. The study also aimed to discover if rural and urban inhabitants have similar perspectives on Airbnb impacts. Airbnb’s entrepreneurial encroachment into the accommodation sector has caused a multitude of localities to manage an assortment of complex affairs. These matters are difficult to solve due to their changing, contradictory, and incomplete premise. The purpose of this research is to determine if Airbnb activity is prominent in Iceland and therefore causing the country to experience similar issues that officials are struggling to solve in many major cities worldwide. This was established by running descriptive statistics on data obtained through a voluntary survey. This research can aid in creating international legislative platforms to maximize the benefits and minimize the risks related to Airbnb, as matters in Iceland can show similarity to other global cities. Locally, the results discovered in Iceland will be valuable to the Icelandic Tourist Board’s ongoing research on tourism trends within the island. Tourism was pushed as a tool in Iceland after the 2008 financial crisis in response to the country’s failing fishing and aluminum industries. Tourism now accounts for upwards of 10 percent of Iceland’s Gross Domestic Product (GDP). There is a concern for the economic endeavor’s ability to diminish Iceland’s culture and nature, which are what draws tourists initially, making tourism a multiplex theme in Iceland. This research will contribute to the emerging scholarly work on tourism, Airbnb, and their impacts on sensitive polar regions that dictate the rest of the world’s climate such as Iceland.